2007
DOI: 10.1002/jcp.20982
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the underlying genetic and epigenetic events leading to gastric carcinogenesis

Abstract: Gastric cancer is a common aggressive malignancy. Although its incidence shows considerable variation among different countries, gastric cancer is still a major health problem worldwide. The causes of stomach cancer are not completely understood. What is clear is that gastric cancer is a multi-stage process involving genetic and epigenetic factors. This review is an in-depth study of the known genetic and epigenetic processes in the development of this tumor, and delineates possible approaches in gene and epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
76
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 107 publications
0
76
0
Order By: Relevance
“…Several environmental factors, including Helicobacter pylori infection, consumption of salted and nitrated foods, and cigarette smoking, have been found to be associated with the risk of developing GC [6][7][8][9]. In addition to environmental factors, genetic factors also play an important role in GC etiology, and previous reports suggest that combinations of genetic and/or epigenetic changes in oncogenic and tumor suppressor pathways may drive GC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several environmental factors, including Helicobacter pylori infection, consumption of salted and nitrated foods, and cigarette smoking, have been found to be associated with the risk of developing GC [6][7][8][9]. In addition to environmental factors, genetic factors also play an important role in GC etiology, and previous reports suggest that combinations of genetic and/or epigenetic changes in oncogenic and tumor suppressor pathways may drive GC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, promoter hypermethylation of tumour-related genes has also been proposed as a novel biomarker for detecting cancer and predicting prognosis (Jones and Baylin, 2007). We and others have shown earlier that many tumour-related genes were frequently silenced through promoter hypermethylation in gastric carcinoma as well as pre-malignant gastric lesions (Leung et al, 2001; Lee et al, 2002;To et al, 2002;Chan et al, 2004;Choi and Wu, 2005;Chan and Rashid, 2006;Sato and Meltzer, 2006;Cheng et al, 2007;Ushijima, 2007;Vogiatzi et al, 2007), suggesting that promoter hypermethylation can be utilised as biomarkers for early detection of gastric cancer.…”
mentioning
confidence: 99%
“…Although with variations in prevalence, these studies revealed somatic mutations in both genes that might be relevant in gastric carcinogenesis [50][51][52][53][54][55] . In addition to multiple genetic alterations, the initiation and progression of gastric cancer are also associated to epigenetic changes [56,57] . Histone modification and promoter CpG methylation alter cancer-related gene expression and are frequently involved in carcinogenesis [58] .…”
mentioning
confidence: 99%